(untitled) (International Seven Journal of Multidisciplinary, 2026)
Vasospastic angina (VSA) is a clinically relevant entity within the spectrum of ischemic syndromes with non-obstructive coronary arteries, characterized by transient vasoconstriction of the epicardial and/or microvascular coronary bed, with variable ischemic repercussions. Although often associated with chest pain at rest and transient electrocardiographic changes, its presentation may mimic acute coronary syndromes and culminate in malignant arrhythmias, myocardial infarction, and sudden death. Diagnosis remains challenging, particularly when coronary angiography does not reveal significant lesions, requiring high clinical suspicion and, in selected centers, provocative testing with acetylcholine and/or ergonovine. In treatment, calcium channel blockers constitute the therapeutic cornerstone, with nitrates as adjunctive agents. Controversies persist regarding the role of antithrombotic therapies in VSA without obstructive atherosclerosis, especially concerning the routine use of aspirin. Recent evidence reinforces the importance of a guided approach incorporating assessment of vasomotor dysfunction and inflammatory biomarkers, as well as potential genetic implications. This narrative review synthesizes contemporary evidence on diagnosis, first-line therapies, the rationale and limitations of antithrombotic use, and the impact of inflammation on pathophysiology, pointing to future perspectives for more precise and individualized management.